'Total Germany' the Royal Navy's war against the Axis powers, 1939-45 - Wragg, David W. (Skyhorse Publishing, 2015)
Covers the Second World War Operations of the Royal Navy in One Concise Volume On the declaration of war in 1939, the British Admiralty signaled all warships and naval bases: #x93;Total Germany, Total Germany." It was fortunate that of Germany's three armed services, the Kriegsmarine, under Grosseradmiral Erich Raeder, was the least well prepared. They had not expected to fight all-out war for another two to three years. While Admiral Karl Dönitz's U-boat force was to give the Allies much anxiety, Hitler was never comfortable or competent in his handling of naval surface forces